2006
DOI: 10.1097/01.olq.0000218881.01437.99
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Among Female Sex Workers in Southwestern China: Potential for HIV Transmission

Abstract: High prevalence of syphilis and overlapped unprotected commercial sex and drug using behaviors among FSWs along a drug-trafficking route may suggest a potential for rapid spread of HIV from injection drug users to FSWs and then to the general population and underscore the urgency of preventive interventions to break the bridge of FSWs for HIV/sexually transmitted disease spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 11 publications
6
78
4
Order By: Relevance
“…It varied from 14.2% in the US-Mexico border cities to 45.7% in Argentina [1,12,[18][19][20][21][22] . This varied prevalence rates may be due to the different population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It varied from 14.2% in the US-Mexico border cities to 45.7% in Argentina [1,12,[18][19][20][21][22] . This varied prevalence rates may be due to the different population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The STI rate in our sample was similar to that in previous studies of FSWs in China. 13,18 Because there was no prior study that compared self-reported and biologically tested STI in FSWs in China, it is difficult to judge the extent of underreporting. However, a study conducted in drug-using FSWs in Amsterdam reported 34% underreporting of STI, 11 and a study with sexually active adolescents recruited from clinics in the United States found underreporting of STI to be 21%-47%.…”
Section: Discussionmentioning
confidence: 99%
“…However, demographic characteristics reported by our participants were similar to those observed in previous studies with different sampling methods. 13,17,18 Second, data about the history of STI testing were not available in the current study. Therefore, we could not further break down underreporting subjects into those who were tested before and those who were never tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, though HIV prevalence rates vary among some Chinese high risk populations such as sex workers [5][6][7], men who have sex with men [8][9][10] and former plasma donors [11][12], incidence is low or lacking [13], only IDUs cohorts in southwestern and northwestern Chinese provinces such as Sichuan, Guangxi and Xinjiang have shown high HIV incidence rates from 3.1 to 8.8% and moderate 12-month retention rates from 70 to 93% [14][15][16]. Typically, a cohort with <2% HIV seroincidence and <90% 1-year retention is considered inappropriate for phase III vaccine trials, because in this situation the sample size required would be too large for an effect to be shown.…”
Section: Introductionmentioning
confidence: 99%